Performance of the Trade Service Regarding Supervision of Subsidized Fertilizer Distribution in Balikpapan City - Purnamasari, Andi; Anwar, Khairil; Permanasari, Devi; Totalia, Sherly Sustantien (Pascasarjana Universitas Mataram, 2024)
This study aims to evaluate the Performance of the Balikpapan City Trade Office in supervising the distribution of subsidized fertilizers, which is an important element in supporting the agricultural sector and food security. Subsidized fertilizers play a role in providing access to farmers to obtain fertilizers at affordable prices, but challenges such as uncertainty of supply and uneven distribution are still problems. The research method used is descriptive qualitative with data collection through documentation and interviews. The results of the study indicate that the trade office has implemented integrated and comprehensive supervision standards, including planning, implementation, and monitoring of fertilizer distribution. Although there has been progress in the availability of fertilizers, the evaluation indicates the need for improvements in inter-agency cooperation and distribution systems to increase the effectiveness of supervision. With reports on the circulation of fake fertilizers, the Trade Office conducts direct supervision at kiosks and farmer groups and coordinates with related agencies to ensure effective distribution